Pembingkaian Berita Reklamasi Teluk Benoa di Balebengong.id Periode Agustus 2016 - Sutiawati, Ni Made Hana; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2018)
ABSTRA CT The mass media directs the awareness of the audience to the issues that are considered important by making the process of setting the agenda. One of the issues that is currently developing in the mass media is the issue of reclamation of Benoa Bay. Various news on the reclamation of Teluk Benoa emerged in mainstream media and alternative media with various viewpoints. One of the alternative media that is consistently reporting the development of the issue of Benoa Bay reclamation is Balebengong.id. As an alternative media, Balebengong.id resembles the news of Benoa Bay reclamation in the form of citizen journalism that is not tied to the system as well as mainstream media, so that the published news is considered more neutral and democratic. This research was conducted to find out the framing of news of Benoa Bay reclamation in Balebengong.id by analyzing eight news published in August 2016. This research is a qualitative research using framing analysis method Zhongdang Pan and Gerald M.Kosicki. The results of this study indicated that Balebengong.id more highlight the news about the rejection that appears against the reclamation plan Benoa Bay. Keywords : Balebengong.id, Benoa Bay Reclamation, Frame Analysis Zhongdang Pan and Gerald      M.Kosicki, Citizen Journalism